2018
DOI: 10.1111/rda.13172
|View full text |Cite
|
Sign up to set email alerts
|

Methylation pattern variation between goats and rats during the onset of puberty

Abstract: Puberty is initiated by increased pulsatile gonadotropin-releasing hormone (GnRH) release from the hypothalamus. Epigenetic repression is thought to play a crucial role in the initiation of puberty, although the existence of analogous changes in methylation patterns across species is unclear. We analysed mRNA expression of DNA methyltransferases (DNMTs) and methyl-binding proteins (MBPs) in goats and rats by quantitative real-time PCR (qRT-PCR). DNA methylation profiles of hypothalamic were determined at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
7
0
1
Order By: Relevance
“…This decrease of the global DNA methylation, from Pre- to In-pubertal stage, may be related to the DNA methylation changes of genes which represses the initiating of puberty in Pre-puberty, and these genes may change from transcriptional repressions to activations. Moreover, many DMGs such as NLRC5, SMOC1, GRID1, ABAT, MAP3K4, and PTPRN reported in rat (Yang et al, 2018) and goat (Yang et al, 2018) across the pubertal transition were also identified in this study (Supplementary File S4). Furthermore, changes of the DNA methylation in the hypothalamus were all enriched in Neurotrophin signaling pathway and Estrogen signaling pathway for rat (Yang et al, 2018), goat (Yang et al, 2018)and pigs (Figure 6).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This decrease of the global DNA methylation, from Pre- to In-pubertal stage, may be related to the DNA methylation changes of genes which represses the initiating of puberty in Pre-puberty, and these genes may change from transcriptional repressions to activations. Moreover, many DMGs such as NLRC5, SMOC1, GRID1, ABAT, MAP3K4, and PTPRN reported in rat (Yang et al, 2018) and goat (Yang et al, 2018) across the pubertal transition were also identified in this study (Supplementary File S4). Furthermore, changes of the DNA methylation in the hypothalamus were all enriched in Neurotrophin signaling pathway and Estrogen signaling pathway for rat (Yang et al, 2018), goat (Yang et al, 2018)and pigs (Figure 6).…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, many DMGs such as NLRC5, SMOC1, GRID1, ABAT, MAP3K4, and PTPRN reported in rat (Yang et al, 2018) and goat (Yang et al, 2018) across the pubertal transition were also identified in this study (Supplementary File S4). Furthermore, changes of the DNA methylation in the hypothalamus were all enriched in Neurotrophin signaling pathway and Estrogen signaling pathway for rat (Yang et al, 2018), goat (Yang et al, 2018)and pigs (Figure 6). These observations not only supported the accuracies of findings in the present study but also suggested the patterns of DNA methylation variations were like to be similar among goat, rat and pigs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…GABA is known to regulate reproduction, but it is not known whether GABA-T affects reproductive function by affecting GABA. GABAergic signaling pathways exhibited an association with the initiation of puberty, and GABA-T was significantly increased in pubertal goats compared to prepubertal goats [25,26]. Therefore, we speculated that GABA-T affects reproductive function.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported that changes of DNA methylation cause KISS1 gene, which has emerged as an essential gatekeeper for the onset of puberty via directing the stimulation of GnRH secretion at the hypothalamic level [2022], switching from repressive to permissive in mice [19, 23, 24]. Moreover, the changes and dynamics of genome-wide DNA methylation during the onset of puberty have been described for the hypothalamus of female goats [25, 26] and rats [27], and these studies have provided useful insights into the epigenetic mechanism for the timing of puberty at hypothalamus level for mammals. However, few investigations have focused on the dynamics and changes of DNA methylation in pituitaries during the pubertal transition in mammals.…”
Section: Introductionmentioning
confidence: 99%